ANALISIS STABILITAS BACK-TO-BACK MECHANICALLY STABILIZED EARTH WALLS (STUDI KASUS JALAN LAYANG DI SULAWESI SELATAN) - Yordan Salim; Andryan Suhendra (JMTS: Jurnal Mitra Teknik Sipil, 2021)
In urban areas, the requirement for roads is always increasing. This has resulted in various problems such as limited land so that it needs to construct a proper retaining wall. The type of retaining wall that will be discussed is back-to-back mechanically stabilized earth walls. The author analyzes the minimum reinforcement length required for the stability of the retaining wall structure. The author also analyzes the use of backfill material from back-to-back mechanically stabilized earth walls. In this study, two types of backfill materials were used, sand and laterite. The author analyzes the stability of the structure using manual calculations and with software based on finite element methods with several differences in the reinforcement length of the geogrid. In manual analysis obtained the tensile force that occurs in the geogrid and the safety factor for the external stability. In the analysis using the software obtained the safety factor and deformation that occurs in the structure. The results of this study are the minimum ratio of reinforcement length to height, that is L = 0.66H for sand and L = 0.6H for laterite. The requirement of geogrid tensile capacity for laterite is smaller than for sand.Keywords: reinforcement length, mechanically stabilized earth walls, geogrid, safety factorPada daerah perkotaan, kebutuhan akan jalan selalu meningkat. Hal ini mengakibatkan berbagai masalah seperti keterbatasan lahan sehingga perlu konstruksi dinding penahan tanah yang tepat. Jenis dinding penahan tanah yang akan dibahas adalah back-to-back mechanically stabilized earth walls. Penulis menganalisis panjang penjangkaran minimum yang diperlukan untuk statbilitas struktur dinding penahan tanah. Penulis juga menganalisis penggunaan material timbunan dari back-to-back mechanically stabilized earth walls. Pada penelitian ini digunakan dua jenis material timbunan yaitu pasir dan tanah merah. Penulis menganalis kestabilan dari struktur menggunakan perhitungan manual dan dengan software berbasis metode elemen hingga dengan beberapa variasi panjang penjangkaran dari geogrid. Pada analisis manual, diperoleh gaya tarik yang terjadi pada geogrid dan faktor keamanan dari stabilitas eksternal struktur. Pada analisis menggunakan program diperoleh faktor keamanan dan deformasi yang terjadi pada struktur. Adapun hasil dari penelitian ini yaitu rasio panjang penjangkaran terhadap tinggi minimum yaitu L = 0,66H pada pasir dan L = 0,6H untuk tanah merah. Kebutuhan kapasitas tarik geogrid untuk tanah merah lebih kecil daripada pasir.Kata kunci: panjang penjangkaran, mechanically stabilized earh walls, geogrid, faktor keamanan